Upaya Meningkatkan Mutu Lembaga Pendidikan Melalui Sistem Akreditasi Dalam Perspektif Total Quality Management (TQM) Di SD Muhammadiyah Karangbendo Bantul - Luthfi Zihni Rahman (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
Accreditation is an activity for evaluating the feasibility of a program in an education based on predetermined criteria. This accreditation is applied as an evaluation material and also controls the quality of education. However, even though the accreditation system has been developed and formulated in such a way, not many schools have been able to implement the existing instruments in the accreditation to improve the quality of their educational institutions. Many schools have not utilized the existing systems and instruments in accreditation optimally. Therefore, the implementation of accreditation in schools also requires an approach so that the process can run optimally. That approach is called by Total Quality Management (TQM). This research is a qualitative descriptive study. Data collection techniques through observation, documentation, and interviews. The results of this study found that accreditation in the TQM perspective contains the principles, among others: First, accreditation contains standards that are used as reference for implementation; Second, the school utilizes the assessment instruments that are in the accreditation to monitor the ongoing education services (monitoring and evaluation); Third, school accreditation is used to identify deficiencies in schools (deviations); Fourth, accreditation is used as a reference to continuously improve the quality of their schools.